ORGANIZATION AND DESIGN OF RESIDENTIAL BUILDINGS IN CONSTRUCTION - Solijonov Javoxirmirzo Obidjon o‘g‘li; Normirzayev Avazxon Akram o‘g‘li; Kamilova Omina Zoxidjon qizi (Journal of Geography, Regional Planning and Development, 2024)
Construction design for materials own into takes one series standard to constructions based on citizenship buildings construction in engineering used elements and systems . They are with one in line in the textbook experimental designs shown leader project institutions and persons by work issued foreign companies